EFEKTIVITAS USABILITY (PENGGUNAAN) SIGN SYSTEM RSUD MAYJEN H. A. THALIB KERINCI - ARNO JONER, Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The selection of the Sign System at the General Hospital of Mayjen. H. A. Thalib Kerinci for the object of the research was carried out with the background of the many visitors to the hospital, so that it needed a media information sign system in the hospital. The research objective of RSUD Mayjen H.A. Thalib Kerinci to find out the extent to which the effectiveness of Usability (usage) information media Sign System RSUD Mayjen H. A. Thalib Kerinci. The method used in this study is qualitative descriptive. Qualitative research design is to understand the events experienced by what is studied to get data in accordance with the conditions that occur. The subjects of this study were visitors to the General Hospital of Mayjen H.A. Thalib Kerinci, amounting to 3 people as informants or resource persons. This study uses data collection techniques by means of observation, interviews with informants, and documentation.The results of the Sign System research at the General Hospital of Major General H. A. Thalib Kerinci were effective. The effective results of the sign system at RSUD Mayjen H.A. Thalib Kerinci obtained from the results of data findings and interviews of informants who gave answers about the sign system at the General Hospital of Major General H.A. Thalib Kerinci has shown the right direction and does not make visitors confused. Illustration of RSUD sign system Mayjen H.A. Thalib Kerinci can be easily understood. The layout of the sign system at RSUD Mayjen H.A. Thalib Kerinci can be seen easily (unhindered) and the location of the placement is in the right place. Sign system at RSUD Mayjen H.A. Thalib Kerinci's condition looks good and can still be understood.Keywords: Effectiveness, Sign system, RSUD Maj. Gen. H.A. Thalib Kerinci.